STUDI MEKANISME DEGRADASI MATERIAL DAN MODUL SEL SURYA SILIKON AMORF - W.Mongan, Satyono
Recently a-Si:H solar cells have received much attention in the last decade. Data of experimental field for two years in Japan show the existence of degradation and recovery phenomena of solar cell module efficiency following the surrounding temperature. In order to predict long-term performance of a-Si:H solar cell module, a model for degradation of a-Si:H solar cell has been 6 constructed based on the rate of metastable defect formation in the material. The constructed model has successfully fit experimental data. Application of this model in Bandung Area suggests the degradation of only about 2.5% from initial efficiency for average temperature of 60Â°C. This result implies that a-Si:H solar cell is appropriate for being used in tropical area